Prototype Model of Marine Pollution Monitoring Using Multiple Remote Sensing Platforms - Yang, Chan-Su; Shin, Dae-Woon (IEEE International Geoscience and Remote Sensing Symposium proceedings, 2023)
Various platforms, such as satellites, manned aircraft, Unmanned Aerial Vehicle (UAV), and mobile devices, can be used to obtain remotely sensed data in the form of images or videos. In this study, we present a prototype model that utilizes multiple remote sensing data for monitoring marine pollution. Our aim is to generate and visualize marine pollution information, which would facilitate swift and precise responses to marine pollution incidents. The automatic production and sharing of Marine Pollution Information (MPI) are crucial steps in effectively addressing on-site oil spills. Of many marine pollutants, oil spills and some floating Hazardous & Noxious Substances (HNS) are the subjects of the work.